Educational needs of newly diagnosed cancer patients in learning about cancer: A qualitative study in the Malaysian urban setting / Murallitharan Munisamy - Murallitharan, Munisamy (2020)
Patients with chronic diseases such as cancer are able to have better outcomes if they understand about all aspects of the disease, develop the correct attitude to manage themselves and their disease better; and engage in preventive practices that can help them prevent worsening of disease or recurrence. Patient education is an intervention that has proven to be effective in different settings for this. However in the Malaysian cancer setting, the educational needs of patients are poorly understood. The aim of this study was to explore and understand the educational needs of newly diagnosed cancer patients in learning about cancer in the Malaysian urban setting. Qualitative, in-depth interviews were carried out via Zoom with 23 cancer patients who were newly diagnosed over the past 6 months and had sought services at the National Cancer Society of Malaysia. The patients reported having specific educational needs at the point of diagnosis, during their treatment journey; and in terms of emotional and psychosocial management. Delivery of patient education included challenges from both the patients themselves as well as system-level delivery. Patients reported that their cancer-related educational needs were partially fulfilled but had suggestions on how to better provide effective patient education. Newly diagnosed cancer patients have educational needs that are being partially fulfilled. Further research and improvement can aid in designing and delivering better educational solutions which can benefit patients.